2011
DOI: 10.1074/jbc.m111.291823
|View full text |Cite
|
Sign up to set email alerts
|

Close-up of the Immunogenic α1,3-Galactose Epitope as Defined by a Monoclonal Chimeric Immunoglobulin E and Human Serum Using Saturation Transfer Difference (STD) NMR

Abstract: Background: Antibody binding to xenobiotic ␣-Gal structures mediates anaphylaxis. Results: Humanized IgE antibodies exhibit recognition footprints similar to serum immunoglobulins but have no capability of effector cell activation. Conclusion: Recognition of the ␣-Gal epitope is based on the terminal disaccharide, but interaction does not imply cellular activation. Significance: These data provide the first insights into the recognition of carbohydrate IgE epitopes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…It appears that binding to α-gal is largely determined by the terminal galactoses, as has been suggested by others [28]; [30]. Specificity to α-gal on the other hand may be also determined by the proximal sugar residues of α-gal and related sugar epitopes, B in particular.…”
Section: Discussionsupporting
confidence: 52%
“…It appears that binding to α-gal is largely determined by the terminal galactoses, as has been suggested by others [28]; [30]. Specificity to α-gal on the other hand may be also determined by the proximal sugar residues of α-gal and related sugar epitopes, B in particular.…”
Section: Discussionsupporting
confidence: 52%
“…Using nuclear magnetic resonance, it has been confirmed that the antibodies are primarily directed at the 2 terminal galactoses. 26 The ongoing IgG Ab response to α -gal, thought to be induced by continuous antigenic stimulation in the gut, is predominantly IgG2. 27 After tick bites, the IgG antibodies increase in parallel with IgE antibodies, but they are predominantly IgG1.…”
Section: Development Of Ige To α-Gal Responsementioning
confidence: 99%
“…Using NMR, it has been confirmed that the antibodies are primarily directed at the two terminal galactoses [20]. It is important to remember that all immuno-competent humans (as well as Old World monkeys and apes) have circulating IgG antibodies to alpha-gal [21].…”
Section: Ticks and Ige Antibody Responsesmentioning
confidence: 99%